2016
DOI: 10.1021/acs.jafc.6b04367
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Maillard Reaction Product [5-(5,6-Dihydro-4H-pyridin-3-ylidenemethyl)furan-2-yl]methanol (F3-A) in Breads and Demonstration of Bioavailability in Caco-2 Intestinal Cells

Abstract: [5-(5,6-Dihydro-4H-pyridin-3-ylidenemethyl)furan-2-yl]methanol, also called F3-A, has been isolated from hexose-lysine Maillard reaction (MR) models. Here we report on optimized conditions for the recovery of F3-A and concentrations found in bread. Recovery of F3-A was best achieved when samples were extracted with dichloromethane (DCM) at a solvent to sample ratio of 2:1 (v/v) after adjustment of the pH to 12. The amount of F3-A in whole wheat bread was significantly (P < 0.05) higher than that in white bread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…In similar studies, Rodriguez-Hernandez et al performed in vitro digestion of different cultivars of raw freeze-dried broccoli and measured corresponding levels of glucoraphanin and sulforaphane. Both glucoraphanin and sulforaphane decreased during digestion of broccoli florets (cv.…”
Section: Resultsmentioning
confidence: 99%
“…In similar studies, Rodriguez-Hernandez et al performed in vitro digestion of different cultivars of raw freeze-dried broccoli and measured corresponding levels of glucoraphanin and sulforaphane. Both glucoraphanin and sulforaphane decreased during digestion of broccoli florets (cv.…”
Section: Resultsmentioning
confidence: 99%
“…Propranolol is a high permeability-high solubility lipophilic drug that can be completely absorbed after oral consumption (bioavailability of > 90%). In contrast, furosemide is a low permeability-high solubility hydrophilic drug with a low bioavailability of 10–60% [ 12 , 31 ]. Based on these two extremes for estimating bioavailability, we further confirmed that troxerutin and rutin have low bioavailability, as their P app value was lower than that of furosemide.…”
Section: Resultsmentioning
confidence: 99%
“…The absorptions of troxerutin and its acylated derivatives was measured as described by Chen et al [ 12 ]. Caco-2 cells were cultured in DMEM supplemented with 10% FBS, 100 μg/mL streptomycin, and 100 U/mL penicillin at 37 °C in an atmosphere of 5% CO 2 and the medium was changed every 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although correlation does not prove causation, it might be postulated that the CML detected in infants is derived from dipeptide-bound CML or that the Caco-2 cell model is not representative for the immature gut wall of infants. A higher percentage of fecal excretion (22–48%) compared to urinary excretion (7–38%) in rats has been observed for CML, but in vitro and in vivo studies have also shown that CML can be degraded by human gut microbiota by up to 40%, suggesting that CML can be degraded in humans and used as sources of energy, carbon, and nitrogen. , The AGE [5-(5,6-dihydro-4 H -pyridin-3-ylidenemethyl)­furanyl]­methanol, which is proposed to be formed by a condensation between HMF and 1,2-dihydropiperidine (formed from the Strecker aldehyde of lysine, 5-aminopentanal, via a cyclization), has recently been detected in bread and found to be transported across Caco-2 cell monolayers, suggesting bioavailability of this AGE . The large variation in uptake patterns and mechanisms of AGEs clearly shows an urgent need for molecular characterization of the chemical composition of AGEs formed in foods to understand how AGE formation affects the nutritional composition of our diet and our health.…”
Section: Introduction To Maillard Reactions In Foodsmentioning
confidence: 99%